Metabolic stress and cancer: is autophagy the common denominator and a feasible target? - Giuliani, C.; Dass, Crispin (John Wiley & Sons Ltd., 2014)
Objectives: Autophagy facilitates the degradation of proteins or organelles into recyclable molecules, which are released into the cell to foster cell survival under energetic stress. Furthermore, autophagy has been associated with cancer cell survival and chemoresistance, and as such, it is an area of increasing interest. As autophagic activity and its regulation are related to metabolism and energy stress,it is critical to elucidate the exact molecular mechanisms that drive it. Key findings: Cancer is recognised to have specific metabolic changes, which include the switch from oxidative phosphorylation to glycolysis. Although the exact rationale is yet to be determined, it is proposed to limit hypoxic stress and generate substrates for biosynthesis. The various forms of energetic stress including hypoxia, glucose and amino acid deprivation have been reviewed in relation to their effect on autophagy and certain key molecules identified to date. These key molecules, which include AMP-activated protein kinase, mammalian target of rapamycin complex 1, adenosine triphosphate and reactive oxygen species, are all implicated as key stimuli of autophagic activity, as will be discussed in this review. Summary: These findings indicate that autophagic regulation could be a means to better cancer treatment.